Twofold Ferrocene C–H Lithiations For One-Step Difunctionalizations - Erb, William; Mongin, Florence (Synthesis, 2019)
For some aromatics, a twofold C–H deprotolithiation can be achieved, allowing these compounds to be subsequently difunctionalized in one step. This short review brings together examples in which ferrocenes are converted in this way.1 Introduction2 Bare Ferrocene3 Ferrocenes Substituted by Alkyl or Silyl Groups4 Ferrocenes Substituted by Aminoalkyls5 Ferrocenes Substituted by Halogens or Oxygen-Based Groups6 Ferrocenes Substituted by Alkoxyalkyls or Acetals7 Ferrocenes Substituted by Sulfoxides8 Ferrocenes Substituted by Oxazolines9 Ferrocenes Substituted by Carboxamides10 Conclusion
Keywords: ferrocene; deprotolithiation; dilithio compounds; electrophilic trapping; planar chirality; chiral directing group; chiral ligand; ferrocenophane